Study guides

Q: Simplify 2a plus 3b plus 5a plus 6 plus 3b?

Write your answer...

Submit

Related questions

Add them together: 2a+5a = 7a

-6(a-3b-9c)

-2a plus 3b

2a² + 6a

2a + 10 + 5a - 2 = (2a + 5a) + (10 - 2) = 7a + 8

2a + 11a - 5a = 8a

No

2a + 3b

2a + 4b

20a2b2

5a + 11

5a³ - 4ab + 2a³ = (5+2)a³ - 4ab = 7a³ - 4ab.

12a + 6b + 6c = 6(2a + b + c)

2a

2a+5

2a + 3a + 4 = 5a + 4

2a+5a+9a = 16a

2a + 5a + 3a = 10a

Gathering like terms together, this is equal to 5a + 3b + 7c.

3a4 - 2a2 + 5a - 10 - 2a4 + 4a2 + 5a - 2 = a4 + 2a2 + 10a - 12 = a4 + (2a - 2)(a + 6)

9a +8 -2a -3 -5a = 2a +5

The value of a in the equation 5a plus 2a = 6-6a is a=6/11.

5a + 3 + (2a - 2) + a= 5a + 3 + 2a - 2 + a= 8a + 1

(5a - 4b) + (2c - 3b - 6c) + a =5a - 4b + 2c - 3b - 6c + a =(5a + a) + (-4b - 3b) + (2c - 6c) =[ 6a - 7b - 4c ].

2a + 3a = 5a